PROFIL KEBUTUHAN PSIKOLOGIS TARUNA/I AKADEMI TEKNIK DAN KESELAMATAN PENERBANGAN MEDAN - syafruddin, yano; Hutabarat, Liber Tommy; Diriyanti Novalina, Susi; Sinaga, Yustian (Psychology Department Faculty of Psychology Universitas Medan Area, 2016)
This study aimed to determine the profile of the psychological needs Taruna ATKP Terrain Data cadets some 177 people gathered with the use of psychological tests EPPS are then processed using descriptive statistics. The results showed that the needs of the dominant owned by the cadets is the need of Intraception (placement up to others/empathy), need of dominance (lead/influence), need of abasement (willingness to accept mistakes), Need of Nurturance (attention and feeling warm towards others). Psychological needs were classified as moderate is the need of achievement (accomplishment), need of deference (the ability to adapt), need of order (task with regular/tidy), need of exhibition (present themselves), then psychological needs are likely to be low is need of autonomy (self-behavior), need of succorance (for help/assistance), need of heterosexual and need of aggression (aggressiveness).